Impact of Aerobic Exercise and Acupuncture Treatment on Obese Patients; A Retrospective Case-Controlled Study - Yılmaz Sezgin; Aşkın Keskin Kaplan (Korean Pharmacopuncture Institute, 2021)
Objectives: The purpose of this study is to investigate the effects of aerobic exercise and acupuncture treatment in obese patients. Methods : : The effects of exercise in obese patients receiving acupuncture therapy were investigated in this retrospective, case-controlled study in which subjects complying with exercise were enrolled in the case and non-compliers were enrolled in the control group.Results : : There was a statically significant weight loss in both the study case group (94.39 ± 20.36; 88.91 ± 19.00; n = 22; p = 0.001) and the control group (103.18 ± 21.92; 99.56 ± 21.92; n = 34; p = 0.001) after 3 months. Weight loss occurred in all 22 patients in the case group. In the control group, while weight loss occurred in 27 of the 34 patients, weight gain occurred in three patients. Conclusion : : In conclusion, the addition of modalities such as acupuncture, exercise and diet may provide effective improvement in weight control.